Isolation of a tumor neoantigen specific CD8+ TCR from a skin biopsy of a vaccination site - Maria Paula Roberti; Pornpimol Charoentong; Yanhong Lyu; Marten Meyer; Stefan B. Eichmüller; Patrick Schmidt; Frank Momburg; Miray Cetin; Felix Hartmann; Nektarios A. Valous; Albrecht Stenzinger; Laura Michel; et al. (OncoImmunology)
T cells that recognize tumor-specific mutations are crucial for cancer immunosurveillance and in adoptive transfer of TILs or transgenic-TCR T cell products. However, their challenging identification and isolation limits their use in clinical practice. Therefore, novel approaches to isolate tumor-specific T cells are needed. Here, we report the isolation of neoantigen-specific CD8+ T cells from a vaccination site of a metastatic breast cancer patient who received a personalized vaccine. Based on the somatic mutations, potential MHC binding epitopes were predicted, of which 17 were selected to generate a peptide vaccine. Cutaneous biopsies were processed after the fifth vaccination cycle to obtain infiltrating lymphocytes from the vaccination site (VILs). IFNγ ELISpot revealed reactivity to four peptides used in the vaccine. Reactive T cells from VILs were non-overlapping with those detected in the blood and the tumor-microenvironment. ScTCR Seq analysis revealed the presence of a clonotype in VILs that further expanded after a round of in vitro stimulation and validated to be specific against a private mutation, namely NCOR1L1475R, presented in the context of HLA-B * 07:02, with no reactivity to the wild-type peptide. Our study shows, for the first time, that tumor mutation – specific T cells are generated at high frequencies in the vaccination site and can be isolated with standard methods for TCR screening. The easy and safe accessibility of skin biopsies overcomes the major hurdles of current TCR screening approaches and present exciting opportunities for the development of innovative immunotherapeutic strategies.